2014
DOI: 10.18632/oncotarget.2476
|View full text |Cite
|
Sign up to set email alerts
|

RNA sequencing identifies specific PIWI-interacting small non-coding RNA expression patterns in breast cancer

Abstract: PIWI-interacting small non-coding RNAs (piRNAs) are genetic and epigenetic regulatory factors in germline cells, where they maintain genome stability, are involved in RNA silencing and regulate gene expression. We found that the piRNA biogenesis and effector pathway are present in human breast cancer (BC) cells and, analyzing smallRNA-Seq data generated from BC cell lines and tumor biopsies, we identified >100 BC piRNAs, including some very abundant and/or differentially expressed in mammary epithelial compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
148
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(158 citation statements)
references
References 30 publications
9
148
0
1
Order By: Relevance
“…PIWI family proteins have been shown to be aberrantly expressed and associated with poor prognosis in ovarian, colorectal, gastric, hepatocellular, esophageal, and pancreatic cancers (13)(14)(15)(16)(17)(18), and piRNA expression has been observed in bladder, colon, lung, cervical, breast, hepatocellular, and gastric cancers (19)(20)(21)(22)(23)(24). Our recent study also identified a genetic variant in a mature piRNA sequence that is associated with breast cancer risk (25).…”
Section: Introductionmentioning
confidence: 69%
“…PIWI family proteins have been shown to be aberrantly expressed and associated with poor prognosis in ovarian, colorectal, gastric, hepatocellular, esophageal, and pancreatic cancers (13)(14)(15)(16)(17)(18), and piRNA expression has been observed in bladder, colon, lung, cervical, breast, hepatocellular, and gastric cancers (19)(20)(21)(22)(23)(24). Our recent study also identified a genetic variant in a mature piRNA sequence that is associated with breast cancer risk (25).…”
Section: Introductionmentioning
confidence: 69%
“…In breast cancer, PIWIL2 and PIWIL4, not PIWIL1 and PIWIL3, had high expression levels in clinical patients [60]. In gastric cancer, the expression of PIWIL1-4 was significantly correlated with the T-stage, lymph node metastasis and clinical TNM (cTNM), and elevated PIWIL1 and PIWIL2 expressions were associated with poorer overall survival, and PIWIL1 expression was suggested to be an independent prognostic factor [39].…”
Section: Piwis May Be Biomarkers For Cancer Diagnosis and Prognosismentioning
confidence: 99%
“…Through deepsequencing analysis of the breast cancer transcriptome, Hashim et al identified numerous piRNAs that are differentially expressed in breast cancer cell lines and tumor biopsies when compared with normal counterparts. The potential mRNA targets for cancer-specific piRNAs were also analyzed [170]. Through genotypic screening of a panel of single-nucleotide polymorphism (SNP)-containing piRNAs, Fu et al [171] identified the breast cancer-specific variant of piR-021285 with SNP rs1326306 .…”
Section: Cd24mentioning
confidence: 99%